Trade offer crisis: a case study on trade offer crisis of Square Toiletries Ltd which is handled by Square - Fatema, Kaniz (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.